PENGGUNAAN MEDIA KEMASAN UNTUK KETERAMPILAN MENULIS TEKS PROSEDUR MURID SD - Fathur Rohman; Dian Indihadi (STKIP Subang, 2026)
Students’ ability to write procedural texts at the elementary school level remains relatively low, particularly in organizing steps systematically, understanding text structure, and applying appropriate language features. This condition indicates the need for contextual and meaningful instructional innovation. This study aims to analyze the use of packaging media as an alternative instructional medium to improve elementary students’ procedural text writing skills. The research employed a descriptive qualitative approach using a library research design. Data were collected through a systematic review of relevant scholarly journals, books, and academic sources published within the last ten years. Data analysis was conducted using content analysis and comprehensive synthesis of previous research findings. The results indicate that packaging media possess authentic, contextual, and multimodal characteristics aligned with the structure of procedural texts, including objectives, materials, and sequential steps. Previous studies also demonstrate that the use of concrete and visual media enhances students’ understanding of text structure, ability to organize steps logically and systematically, as well as learning motivation and participation. Therefore, packaging media have strong potential as an innovative and effective instructional medium for improving elementary students’ procedural writing skills